SOCIO-ECONOMIC CHARACTERISTICS INFLUENCING SUGAR CONSUMPTION PATTERN IN BAUCHI STATE NIGERIA - Mohammed, R.; Murtala, N.; Danwanka, H. A.; Haruna, U. (Nigerian Journal of Agriculture and Agricultural Technology, 2023)
The study examined household sugar consumption pattern in Bauchi State, Nigeria. Cross –sectional data were collected from 412 households using multistage sampling technique. The data were analyzed using descriptive statistics, Linear regression model and budget share index. The socio-economic factors influencing sugar consumption in northern zone of Bauchi State were; age, household size (P<0.01), income (P<0.05), educational level and primary occupation (P<0.1), with R2 value of 0.685. The significant variables that influenced household sugar consumption in central zone were monthly income (P<0.05), cost of sugar and household size (P<0.01) and average monthly total food expenditure (P<0.05); with R2 value of 0.497. In the western zone sugar consumption was influenced by average monthly income and household size (P<0.01), cost of sugar (P<0.05), and primary occupation (P<0.1) with an R2 value of 0.375 and the F-value of all the three zones were significant (P<0.01). The central zone had the highest sugar budget share of 8.70%, followed by western zone (6.59%), while Northern zone had 5.20%. The result showed that, in northern zone the respondents spent 60.91% of their household budget on food, while in central and western zones it was 59.27% and 55.06% respectively. Most of the respondents, 89.4% and 84.2% in central and western zones, respectively reported price as a major constraint to sugar consumption; likewise, 79.7% in northern zone. Income is the second constraint to sugar consumption in all the three zones with 73.4%, 84.6% and 77.6% in northern, central and western zones, respectively. Household size ranked third, the northern zone had 51.0%, central zone 47.1% and western zone 32.7%. A small percentage of the respondents reported health as a constraint to sugar consumption, northern zone 23.1%, central 25.0% and western zone 24.2%. The research concluded that socioeconomic factors have an influence on sugar consumption of the household. The study therefore, recommended Policies and programs toward sugar sector in Nigeria should be improve and implemented toward self-sufficiency in sugar production. Thus, filling the demand and supply gap of the product in the country.